2019
DOI: 10.3390/jmse8010004
|View full text |Cite
|
Sign up to set email alerts
|

Local Scour for Vertical Piles in Steady Currents: Review of Mechanisms, Influencing Factors and Empirical Equations

Abstract: Scour induced by currents is one of the main causes of the bridge failure in rivers. Fundamental knowledge and mechanisms on scour processes due to currents are often taken as a basis for scour studies, which are the focus of this review. Scour development induced by waves and in combined wave–current conditions are also briefly discussed. For the design of structure foundations, the maximum scour depths need to be estimated. The mechanisms of local scour and predictions of maximum local scour depths have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 83 publications
(221 reference statements)
2
16
0
1
Order By: Relevance
“…For example, similar maximum scour depths for both non-cohesive and cohesive sediments under similar flow conditions have been reported [5,7]. Other studies have reported lower or even higher maximum scour depths for cohesive soils compared to non-cohesive soils [8,9,[24][25][26][27][28].…”
Section: Review: Riverbed Scour Depth Equations For Bridge Piers In C...supporting
confidence: 66%
See 1 more Smart Citation
“…For example, similar maximum scour depths for both non-cohesive and cohesive sediments under similar flow conditions have been reported [5,7]. Other studies have reported lower or even higher maximum scour depths for cohesive soils compared to non-cohesive soils [8,9,[24][25][26][27][28].…”
Section: Review: Riverbed Scour Depth Equations For Bridge Piers In C...supporting
confidence: 66%
“…The influence of time dependency of scour development in non-cohesive sediment have been considered in numerous studies [24][25][26][27]. Several studies have also investigated the influence of flow duration, flow magnitude, and flow frequency on erosion behavior of cohesive soil, including the influence on bank erosion, fluvial erosion (channel incision), and localized scour around structures [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Various factors likely contribute. Firstly, the causes that trigger scour hole formation include turbulent flows induced by river bends (e.g., Engelund, 1974;Zimmermann and Kennedy, 1978;Odgaard, 1981;Andrle, 1994;Gharabaghi et al, 2007;Blanckaert, 2010;Beltaos et al, 2011;Ottevanger et al, 2012;Vermeulen et al, 2015), confluences (e.g., Mosley, 1976;Kjerfve et al, 1979;Best, 1986;Ginsberg and Perillo, 1999;Pierini et al, 2005;Best and Rhoads, 2008;Ginsberg et al, 2009;Ferrarin et al, 2018), local channel narrowings and structures, like bridge piers, groynes and bed protection (e.g., Wang et al, 2017;Pandey et al, 2018;Liang et al, 2020). These types of scour holes evolve differently, have different shapes, and as a result have different relations for predicting their equilibrium depth (Hoffmans and Verheij, 1997).…”
Section: Lithological Control On Scour Hole Formationmentioning
confidence: 99%
“…With their steep slopes and large depths, these scour holes can threaten the stability of nearby infrastructure like embankments, bridge piers, tunnels and pipelines (e.g. Gharabaghi et al, 2007;Beltaos et al, 2011;Wang et al, 2017;Pandey et al, 2018;Liang et al, 2020). The formation and development of local scour, bend scour, and confluence scour are widely studied (e.g., Engelund, 1974;Mosley, 1976;Zimmermann and Kennedy, 1978;Kjerfve et al, 1979;Odgaard, 1981;Best, 1986;Andrle, 1994;Ginsberg and Perillo, 1999;Pierini et al, 2005;Gharabaghi et al, 2007;Best and Rhoads, 2008;Blanckaert, 2010;Beltaos et al, 2011;Ottevanger et al, 2012;Vermeulen et al, 2015;Wang et al, 2017;Ferrarin et al, 2018;Pandey et al, 2018;Liang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The material is placed around the foundation of the turbine (e.g., around the monopile) with a radius typically reaching up to 20 m [34,35]. The size and design of the scour protection is determined by a range of environmental factors (i.e., wave and current activity, water depth, sediment characteristics), as well as structural factors (i.e., monopile diameter and design) [36,37] (Figure 1). Generally, the size of the scour protection area reflects the area of the scour pit that would arise due to the environmental factors (e.g., current speed), if the foundation was left unprotected [31], which is usually four to five times the monopile diameter [38].…”
Section: Introductionmentioning
confidence: 99%